Discussion on the future development trend of China’s iron and steel industry under the background of double carbon - Zhifeng CUI; Fangqin SHANGGUAN; Wenlue MA; Xiao LI; Zhengdong LIU; Ruiyu YIN (工程科学学报)
The iron and steel industry is critical to the pursuit of green and low-carbon development. It is strategically important to explore pathways for the industry’s low-carbon transformation. This study constructs a forecast model for various parameters such as crude steel output, scrap steel resource output, carbon emissions, ferrous resource structure, production process structure, and energy consumption structure in the steel industry. It sets up three scenarios to explore the low-carbon transformation path of the steel industry from a strategic perspective. The research results indicate that with adjustments and optimization of the industrial structure, China’s steel industry will trend toward reduced development in the future, with the total output of crude steel expected to decrease annually. By 2060, crude steel production is projected to fall to 600–700 million tons. With the continuous increase in social steel accumulation, the output of scrap steel resources will grow rapidly and is expected to reach a peak around 2045 at approximately 500–600 million tons. With the rational implementation of various carbon reduction measures, the industry’s CO2 emissions are expected to decline steadily each year. By 2060, the steel industry is estimated to still emit 90–198 million tons of CO2. At this stage, achieving “carbon neutrality” will necessitate technologies such as carbon capture, utilization, and storage (CCUS) and carbon sinks. Despite slight differences in carbon reduction amounts among the three scenarios, the overall carbon reduction trends remain similar. The low-output scenario aligns best with the “dual carbon” goals. Under the low-production scenario, the steel industry’s low-carbon development process can be roughly divided into four stages: initial decarbonization, intensified decarbonization, deep decarbonization, and near-zero carbon emission. Among various carbon reduction measures, controlling crude steel production emerges as the most effective carbon reduction measure, contributing approximately 40% of the total carbon reduction potential. The second most effective measure is the utilization of scrap steel resources, with a potential for carbon reduction of about 27%. In addition, process structure optimization and low-carbon technology applications account for 16% and 15%, respectively, indicating their significant roles in carbon reduction. In the future, as China pursues its “dual carbon” goals in the steel industry, the industry’s iron resource structure, production processes, and energy consumption structure will be adjusted and optimized. By 2060, China’s iron ore resource consumption will be reduced by 65%–77% compared to 2023 levels, while scrap steel resource consumption will nearly double. The proportion of the blast furnace-converter process will adjust to 15%–30%, the full-scrap electric furnace process will increase to 40%–50%, and the hydrogen reduction–electric furnace process will rise to 28%–34%. Furthermore, coal resource consumption will decrease by 76%–89%, electricity resource consumption will stabilize at 310–480 billion kWh, and hydrogen resource consumption will reach 10 million tons.